2014
DOI: 10.1007/s11427-014-4698-y
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs and lncRNAs in vascular injury and remodeling

Abstract: Vascular injury, remodeling, as well as angiogenesis, are the leading causes of coronary or cerebrovascular disease. The blood vessel functional imbalance trends to induce atherosclerosis, hypertension, and pulmonary arterial hypertension. As several genes have been identified to be dynamically regulated during vascular injury and remodeling, it is becoming widely accepted that several types of non-coding RNA, such as microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), are involved in regulating the endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 81 publications
1
42
0
1
Order By: Relevance
“…However, lncRNAs show more evolutionarily conserved sequences than intronic and untranscribed intergenic regions, suggesting that most of them are biologically functional in mammals (Bu et al, 2015). Moreover, lnc-RNA expression patterns are strongly associated with diverse key biological processes, such as DNA damage, immune responses, and induced pluripotency, again indicating their potential functionality Song et al, 2014). In terms of the physical localization of lncRNAs relative to protein-coding genes, a subset of lncRNAs is predominantly localized in the nucleus, while the majority exclusively resides in the cytosol.…”
Section: Lncrna Identification and Classificationmentioning
confidence: 99%
“…However, lncRNAs show more evolutionarily conserved sequences than intronic and untranscribed intergenic regions, suggesting that most of them are biologically functional in mammals (Bu et al, 2015). Moreover, lnc-RNA expression patterns are strongly associated with diverse key biological processes, such as DNA damage, immune responses, and induced pluripotency, again indicating their potential functionality Song et al, 2014). In terms of the physical localization of lncRNAs relative to protein-coding genes, a subset of lncRNAs is predominantly localized in the nucleus, while the majority exclusively resides in the cytosol.…”
Section: Lncrna Identification and Classificationmentioning
confidence: 99%
“…Although multiple studies over the last two decades have focused on delineating the molecular mechanisms that drive the remodelling response to vascular injury [11][12][13], with the exemption of drug-eluting stents, there is currently a paucity in effective therapeutics, necessitating further research and innovative thinking around molecular mechanisms that might govern pathological responses According to recent transcriptome analyses, protein-coding genes actually account for only 1.5%-2.0% of the human transcriptome. The transcriptional output of the larger portion of the transcriptome (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[5] miRNAs have been extensively investigated in this respect. For example, miR-210 has been found to promote angiogenesis in HUVEC Matrigel cultures by enhancing the expression of VEGF and VEGFR-2.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Besides miRNAs, recent studies have shown that some lncRNAs also regulate angiogenesis. [5101112]…”
Section: Introductionmentioning
confidence: 99%